2011
DOI: 10.1186/1471-2334-11-107
|View full text |Cite
|
Sign up to set email alerts
|

Performance of whole-blood interferon-gamma release assay in patients admitted to the emergency department with pulmonary infiltrates

Abstract: BackgroundThis study was conducted to evaluate the performance of a whole-blood interferon-gamma release assay in inpatients who were admitted to the emergency department (ED) with pulmonary infiltrates who required a differential diagnosis with pulmonary tuberculosis (TB).MethodsThe patients with pulmonary infiltrates who received a QuantiFERON (QFT) test in the ED were included as an inpatient group and were divided into TB and non-TB group based on the final diagnosis. Patients with pulmonary TB who were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Two studies were conducted in countries with high TB/HIV burden 17,29 and the remaining three studies were conducted in countries with low to intermediate TB burden (Table 1). 21,30,31 Overall, 185 patients (28%) had pulmonary TB, and prevalence ranged from 11 to 93%. Four studies included patients infected with HIV (N=287), 17,21,29,31 including two studies that restricted enrollment to HIV-infected individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were conducted in countries with high TB/HIV burden 17,29 and the remaining three studies were conducted in countries with low to intermediate TB burden (Table 1). 21,30,31 Overall, 185 patients (28%) had pulmonary TB, and prevalence ranged from 11 to 93%. Four studies included patients infected with HIV (N=287), 17,21,29,31 including two studies that restricted enrollment to HIV-infected individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies included patients infected with HIV (N=287), 17,21,29,31 including two studies that restricted enrollment to HIV-infected individuals. 17,21 All studies enrolled hospitalized patients who self-reported symptoms suggestive of TB: 17,21,2931 two studies enrolled patients with pulmonary infiltrates on chest imaging, 30,31 one study enrolled HIV-infected patients with respiratory symptoms, 21 one study enrolled HIV-infected patients with suspected smear-negative pulmonary TB, 17 and one study enrolled patients with fever of unknown origin (FUO). 29 …”
Section: Resultsmentioning
confidence: 99%
“…54e56 Furthermore, it has been reported that pulmonary TB patients with non-positive QFT-TB results have more severe disease than those with positive QFT-TB results, and that the sensitivity of the QFT-TB test may be significantly different depending on disease severity. 57 Therefore, we speculated that the IFN-g production of patients with longer periods of illness before hospitalization may be depressed when stimulated with the M.TB-specific antigens in the T-SPOT.TB test, as is stimulated with sonicated M.TB strains in previous study, 55 and then results in false-negative T-SPOT.TB results in some advanced TB patients. This result is also consistent with some active TB patients showing lower numbers of spot forming cells than individuals with latent tuberculosis infection (LTBI) in the T-SPOT.TB test in clinical situations.…”
Section: Relationship Between Ifn-g Production and The Risk Factors Imentioning
confidence: 96%
“…Among the cytokines secreted, IFN-γ is one of the most studied and has been used as a robust marker for functional immune responses to antigens. [2][3][4][5] Mycobacterial diseases are a primary health concern in humans and animals. Although great progress has been made in the prevention and control of tuberculosis, tuberculosis remains a global health care problem.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Accordingly, the ability to accurately measure antigen‐specific cytokine responses becomes critical to the study of infectious diseases. Among the cytokines secreted, IFN‐γ is one of the most studied and has been used as a robust marker for functional immune responses to antigens …”
Section: Introductionmentioning
confidence: 99%